Teeth restored using fiber-reinforced posts: In vitro fracture tests and finite element analysis - Schmitter, Marc; Rammelsberg, Peter; Lenz, J.; Scheuber, S.; Schweizerhof, K.; Rues, Stefan (Acta biomaterialia, 2010)
In dentistry the restoration of decayed teeth is challenging and makes great demands on both the dentist and the materials. Hence, fiber-reinforced posts have been introduced. The effects of different variables on the ultimate load on teeth restored using fiber-reinforced posts is controversial, maybe because the results are mostly based on non-standardized in vitro tests and, therefore, give inhomogeneous results. This study combines the advantages of in vitro tests and finite element analysis (FEA) to clarify the effects of ferrule height, post length and cementation technique used for restoration.
Gesehen am 15.06.2023